2007
DOI: 10.1109/mdt.2007.152
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Latency-Insensitive Protocols

Abstract: Editor's note Latency-insensitive protocols (LIPs) represent a class of interblock protocols designed to overcome long multiclock interconnects. This article presents an adaptive solution to this problem, which the authors show to be more effective than earlier solutions in terms of power, area, and throughput.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Various implementations exist both in synchronous (e.g., [12]) and asynchronous (e.g., [1], [47]) circuits. Among the different implementations of anti-tokens, two main classes have been distinguished: passive anti-tokens, when they statically wait for the arrival of tokens, and active anti-tokens, when they move backward to meet tokens.…”
Section: A Early Evaluationmentioning
confidence: 99%
“…Various implementations exist both in synchronous (e.g., [12]) and asynchronous (e.g., [1], [47]) circuits. Among the different implementations of anti-tokens, two main classes have been distinguished: passive anti-tokens, when they statically wait for the arrival of tokens, and active anti-tokens, when they move backward to meet tokens.…”
Section: A Early Evaluationmentioning
confidence: 99%
“…The FIC of each channel P i is stored in variable F IC P i (f , g), which is computed by the inner loop (lines 3-10). Then, F IC P i (f , g) is processed based on whether we want to generate the full set of FIC or only SDFIC, which depend only on state variables (lines [11][12][13][14]. The inner loop from lines 3 to 10 performs the main computation of FIC of channel P i .…”
Section: A Background Definitionsmentioning
confidence: 99%
“…The idea has been first investigated in the context of multiclock latency-insensitive circuits in [32] and [33], and it has been applied to elastic systems by using a new latency-insensitive protocol that explicitly encodes antitoken signals [34]. The work by Casu and Macchiarulo on adaptive latency-insensitive protocols [13] and our preliminary results on FIC-based optimization [18] have shown that unnecessary stalling can be avoided with local modification in the logic design of a shell and without requiring any change in the channel interface signals (void and stop bits) that were defined to implement the original latency-insensitive protocol [9].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations